Dioscin alleviates hashimoto's thyroiditis by regulating the SUMOylation of IRF4 to promote CD4+CD25+Foxp3+ treg cell differentiation - Cao Yongjun; Qiao Nan; Sun Yumeng; Jin Xiaowen; Wen Weibo (Taylor & Francis Group, 2021)
Dioscin has been used as a treatment for Hashimoto's thyroiditis (HT) in China. However, the molecular mechanisms governing the modes of action of dioscin have not been elucidated. In this study, flow cytometry and Western blotting were used to identify the proportions of CD4+CD25+ regulatory T (Treg) cells and the expression of forkhead box P3 (Foxp3) and SUMO-specific protease 1 (SENP1) in HT patients' peripheral blood mononuclear cells (PBMCs). A pTg-induced rat model of HT was established by injection of 100 μg pTg. Then, the model rats were randomly divided into three groups (n = 5): control (NC), model (HT) and dioscin treatment. After oral administration of dioscin each day for two weeks, CD4+CD25+Foxp3+ Treg cells were analysed by flow cytometry, and the protein expression levels of SENP1, Foxp3, SUMO-1 and SUMO-2/3 were measured by Western blotting. Co-immunoprecipitation (Co-IP) was used to identify the SUMOylation of interferon regulatory factor 4 (IRF4). The results showed that the proportions of CD4+CD25+ Treg cells and the expression of Foxp3 were significantly decreased in HT patients, but the expression of SENP1 was enhanced compared to healthy controls (HCs). However, compared to the pTg-induced HT rat group, the expression of Foxp3, SUMO-1, and SUMO-2/3 and the proportions of CD4+CD25+Foxp3+ Treg cells were increased, whereas the expression of SENP1 was decreased, in the dioscin-treated group. Furthermore, the SUMOylation of IRF4 was increased after SENP1 was knocked down. The results of our study indicate that dioscin can promote the differentiation of the CD4+CD25+Foxp3+ Treg cells and subsequently upregulate the SUMOylation of IRF4 by downregulating SENP1 expression.